2016
DOI: 10.1177/1758573216632464
|View full text |Cite
|
Sign up to set email alerts
|

Ten questions on prosthetic shoulder infection

Abstract: Prosthetic shoulder infection can cause significant morbidity secondary to pain and stiffness. Symptoms may be present for years before diagnosis because clinical signs are often absent and inflammatory markers may be normal. An emerging common culprit, Propionibacterium acnes, is hard to culture and so prolonged incubation is necessary. A negative culture result does not always exclude infection and new synovial fluid biochemical markers such as a defensin are less sensitive than for lower limb arthroplasty. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…Choice of treatment strategy is largely based on the experiences of treating surgeons and data from hip and knee arthroplasty studies 7 . Though the treatment option depends on the chronicity of infection, organism isolated and its virulence, component stability and patient fitness for surgery 8 , the one- and two-stage revision strategies are preferred as they are associated with successful clearance of infection and good functional outcomes 9,10 . As with PJIs after hip and knee arthroplasty, the two-stage revision strategy is regarded as the standard treatment option for shoulder PJI because it is generally consistently associated with good rates of infection control 10–12 .…”
Section: Introductionmentioning
confidence: 99%
“…Choice of treatment strategy is largely based on the experiences of treating surgeons and data from hip and knee arthroplasty studies 7 . Though the treatment option depends on the chronicity of infection, organism isolated and its virulence, component stability and patient fitness for surgery 8 , the one- and two-stage revision strategies are preferred as they are associated with successful clearance of infection and good functional outcomes 9,10 . As with PJIs after hip and knee arthroplasty, the two-stage revision strategy is regarded as the standard treatment option for shoulder PJI because it is generally consistently associated with good rates of infection control 10–12 .…”
Section: Introductionmentioning
confidence: 99%
“…The infection rate of 3.88% documented in our cohort is comparative to findings of a meta-analysis by Zumstein et al who found an infection rate of 3.8% in RSA patients [ 28 ]. Rates of 1–3.9% have been described for TSA as well [ 29 ], whilst it is thought that rates in RSA patients are higher due to haematoma formation in the increased dead space [ 30 ]. This is in line with our results.…”
Section: Discussionmentioning
confidence: 99%
“…Rates of low-grade infections are often likely to be higher than reported as they are difficult to distinguish from aseptic failure [ 31 ]. Cutibacterium acnes (formerly Propionibacterium acnes), which made up half of our 4 cases, has been reported to be present in 18–60% of infections [ 30 ]. It is found in the deep tissues around the shoulder, more commonly in men, when using the deltopectoral approach and it has been found in the joint fluid of 42% of patients undergoing primary shoulder arthroplasty and more often still in revision surgery [ 30 , 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…46 The occurrence rate of PJI after total shoulder replacement is approximately 1% to 3.9% and can be even higher in reversed designs due to an increase in dead space and hematoma formation. 47 Of all revision shoulder operations, 12% are due to PJI. 47 Because the number of patients who undergo shoulder arthroplasty is growing fast, 46,47 it can be anticipated that the number of patients with PJI also will increase.…”
Section: Role Of Fludeoxyglucose F 18 Positron Emission Tomography Inmentioning
confidence: 99%
“…47 Of all revision shoulder operations, 12% are due to PJI. 47 Because the number of patients who undergo shoulder arthroplasty is growing fast, 46,47 it can be anticipated that the number of patients with PJI also will increase. The value of 18 F-FDG PET in evaluating shoulder PJI, however, has not yet been extensively investigated.…”
Section: Role Of Fludeoxyglucose F 18 Positron Emission Tomography Inmentioning
confidence: 99%